Association between Arsenic Suppression of Adipogenesis and Induction of CHOP10 via the Endoplasmic Reticulum Stress Response - Hou, Yongyong (National Institute of Environmental Health Sciences, 2012)
Background: There is growing evidence that chronic exposure to inorganic arsenic (iAs) is associated with an increased prevalence of type 2 diabetes (T2D). However, the mechanisms for the diabetogenic effect of iAs are still largely unknown. White adipose tissue (WAT) actively stores and releases energy and maintains lipid and glucose homeostasis. Objective: We sought to determine the mechanisms of arsenic suppression of adipogenesis. Methods: The effects and associated mechanisms of iAs and its major metabolites on adipogenesis were determined in 3T3-L1 preadipocytes, mouse adipose-derived stromal-vascular fraction cells (ADSVFCs), and human adipose tissue–derived stem cells (ADSCs). Results: Exposure of 3T3-L1 preadipocytes to noncytotoxic levels of arsenic, including inorganic arsenite (iAs(3+), ≤ 5 μM), inorganic arsenate (≤ 20 μM), trivalent monomethylated arsenic (MMA(3+), ≤ 1 μM), and trivalent dimethylated arsenic (DMA(3+), ≤ 2 μM) decreased adipogenic hormone-induced adipogenesis in a concentration-dependent manner. In addition, iAs(3+), MMA(3+), and DMA(3+) exhibited a strong inhibitory effect on adipogenesis in primary cultured mouse ADSVFCs and human ADSCs. Time-course studies in 3T3-L1 cells revealed that inhibition of adipogenesis by arsenic occurred in the early stage of terminal adipogenic differentiation and was highly correlated with the induction of C/EBP homologous protein (CHOP10), an endoplasmic reticulum (ER) stress response protein. Induction of CHOP10 by arsenic is associated with reduced DNA-binding activity of CCAAT/enhancer-binding protein β (C/EBPβ), which regulates the transcription of peroxisome proliferator-activated receptor γ and C/EBPα. Conclusions: Low-level iAs and MMA(3+) trigger the ER stress response and up-regulate CHOP10, which inhibits C/EBPβ transcriptional activity, thus suppressing adipogenesis. Arsenic-induced dysfunctional adipogenesis may be associated with a reduced capacity of WAT to store lipids and with insulin resistance.